Evaluation of the influence mode on the CVC GaN HEMT using numerical modeling. (August 2016) - Parnes, Ya M; Tikhomirov, V G; Petrov, V A; Gudkov, A G; Marzhanovskiy, I N; Kukhareva, E S; Vyuginov, V N; Volkov, V V; Zybin, A A
Abstract: Done numerically simulated the effects of certain modes of operation on the CVC of field microwave transistors on the basis of heterostructures AlGaN / GaN (HEMT). The results of these studies suggest the possibility of quite efficient use of numerical simulation for the development of HEMT microwave transistors allowing for the real instrument designs.